Fresh brewed murder - Duncan, Emmeline (Duncan, Emmeline. Ground Rules., 2021)
Portland, Oregon. Sage Caplin has high hopes for her coffee cart, Ground Rules. Her business partner, Harley, is a genius at roasting beans and devising new blends. Then Sage finds a customer's body in front of her cart, a fatal slash across his neck. She knows the locals have intensely strong opinions, but who would be mad enough to commit murder? Sage is already fending off trouble in the form of her estranged, con-artist mother, but when her very own box cutter is discovered to be the murder weapon, she needs to focus on finding the killer - fast! -- adapted from back cover